2008
DOI: 10.1902/jop.2008.070132
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Non‐Matching Implant and Abutment Diameters on Radiographic Crestal Bone Levels in Dogs

Abstract: Implants with non-matching implant-abutment diameters demonstrated some bone loss; however, it was a small amount. There was no clinically significant difference between submucosal and transmucosal approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
113
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(143 citation statements)
references
References 22 publications
20
113
1
9
Order By: Relevance
“…In this study the authors used custom-made implants with a FAI micro-gap of 50 m. Similarly, Jung et al 2008 reported that the greatest amount of bone loss occurred in implants placed with the FAI 1mm below the bone crest compared to implants placed with FAI 1mm above or at the level of the bone crest. In this study, implants with non-matching implant abutment diameters were utilized.…”
Section: Position Of the Fixture/abutment Interface In Relation To Thmentioning
confidence: 88%
See 1 more Smart Citation
“…In this study the authors used custom-made implants with a FAI micro-gap of 50 m. Similarly, Jung et al 2008 reported that the greatest amount of bone loss occurred in implants placed with the FAI 1mm below the bone crest compared to implants placed with FAI 1mm above or at the level of the bone crest. In this study, implants with non-matching implant abutment diameters were utilized.…”
Section: Position Of the Fixture/abutment Interface In Relation To Thmentioning
confidence: 88%
“…Placement of the FAI in a more apical position can create an ideal emergence profile for the prosthetic construction (Buser & von Arx 2000). Subcrestal position of the FAI has been reported to have a negative influence on marginal bone level changes in a few animal studies (Jung et al 2008, Hermann et al 2000, Todescan et al 2002, Pontes et al 2008. In an experimental study in dogs Hermann et al 2000 reported that placement of two-part implants with the FAI 1 mm below the crestal bone resulted in pronounced crestal bone loss following 6 months of healing.…”
Section: Position Of the Fixture/abutment Interface In Relation To Thmentioning
confidence: 99%
“…The Inward shifting of the implant-abutment junction (Platform switching) leads to less resorption around dental implants , and this could be explained by the fact that this technique results in a distance between the implant-abutment junction ( microgap) and its associated inflamed connective tissue and the crestal bone (Jung et al, 2008).…”
mentioning
confidence: 99%
“…A análise de SRD promove alta sensibilidade e permite o diagnóstico e detecção de alterações ósseas periodontais ou peri-implantares (Wenzel et al, 1992;Hänggi et al, 2005;Jung et al, 2008;Cochran et al, 2009;De Moraes et al, 2009). No entanto, esta técnica é crítica no quesito desvio da geometria de projeção e alinhamento (Eickholz et al, 2007).…”
Section: Porphyromonas Gingivalis Prevotella Intermédia Actinobacillusunclassified
“…Para refinar o acompanhamento radiográfico deve-se padronizar, geometricamente, as tomadas radiográficas. Isto permite utilizá-las em análises lineares ou de subtração digital, para visualizar variações no rebordo alveolar, tais como formação ou reabsorção óssea peri-implantar (Wenzel et al, 1992;Hänggi et al, 2005;Jung et al, 2008;Cochran et al, 2009;De Moraes et al, 2009), com altas taxas de sensibilidade (94,4%) e especificidade (97,7%) (Jeffcoat, 1992).…”
Section: Introductionunclassified